2011
DOI: 10.1016/j.brainres.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative neuroanatomical and temporal characterization of FluoroJade-positive neurodegeneration after status epilepticus induced by systemic and intrahippocampal pilocarpine in Wistar rats

Abstract: The aims of this study were to characterize the spatial distribution of neurodegeneration after status epilepticus (SE) induced by either systemic (S) or intrahippocampal (H) injection of pilocarpine (PILO), two models of temporal lobe epilepsy (TLE), using FluoroJade (FJ) histochemistry, and to evaluate the kinetics of FJ staining in the H-PILO model. Therefore, we measured the severity of behavioral seizures during both types of SE and also evaluated the FJ staining pattern at 12, 24, and 168 h (7days) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 29 publications
3
32
0
4
Order By: Relevance
“…Due to the high mortality induced by intraperitoneal injection of pilocarpine described in the literature (Curia et al, 2008), we have standardized the model of seizures induced by intrahippocampal injection of pilocarpine in mice, as previously demonstrated in rats (Castro et al, 2011;Furtado Mde et al, 2002). As shown in Table 1 (supplementary data), seventy-five percent of the animals developed SE with a bilateral injection of pilocarpine at the dose of 20 μg/site, albeit no mortality was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high mortality induced by intraperitoneal injection of pilocarpine described in the literature (Curia et al, 2008), we have standardized the model of seizures induced by intrahippocampal injection of pilocarpine in mice, as previously demonstrated in rats (Castro et al, 2011;Furtado Mde et al, 2002). As shown in Table 1 (supplementary data), seventy-five percent of the animals developed SE with a bilateral injection of pilocarpine at the dose of 20 μg/site, albeit no mortality was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in their cell number occurs in some cases of epilepsy (Castro et al, 2011;Dinocourt et al, 2003), Alzheimer's disease (Brady and Mufson, 1997;Takahashi et al, 2010), schizophrenia (Nullmeier et al, 2011;Zhang and Reynolds, 2002), and other disorders such as dementia with Lewis bodies (Bernstein et al, 2011). Although the rhythmicity anti-CR (C day period; D night period), and anti-PV (E day period; F night period).…”
Section: Discussionmentioning
confidence: 99%
“…Pilocarpine has been shown to trigger acute and chronic seizures after intracerebroventricular and intrahippocampal administration (Croiset and De, 1992;Millan et al, 1993;Smolders et al, 1997;Lindekens et al, 2000;Furtado et al, 2002Furtado et al, , 2011Castro et al, 2011;Medina-Ceja et al, 2014). Detailed behavioral, electrophysiological and morphological analyses have been performed in mice by Furtado et al (2002Furtado et al ( , 2011.…”
Section: Intracerebral Injection Of Pilocarpinementioning
confidence: 99%
“…Histopathological studies showed neurodegeneration in the hippocampal CA1, CA3 and hilus subfields, and mossy fiber sprouting in the inner molecular layer of the dentate gyrus. In a recent work, Castro et al (2011) compared neurodegeneration induced by systemic and intrahippocampal administration in rats. The authors found much less extra-hippocampal damage after focal, compared with systemic injection, although neurodegeneration in some cortical regions, the amygdala and thalamus was also observed after intrahippocampal injection.…”
Section: Intracerebral Injection Of Pilocarpinementioning
confidence: 99%